Impact of Androgen Suppression Therapy on the Risk and Prognosis of Bladder Cancer: A Systematic Review and Meta-Analysis - Xiang, Peng; Du, Zhen; Hao, Yongxiu; Guan, Di; Liu, Dan; Yan, Wei; Wang, Mingdong; Liu, Yutong; Ping, Hao (Frontiers in Oncology, 2021)
Purpose: The purpose of this study was to summarize the existing evidence and develop a comprehensive systematic review of the impact of androgen suppression therapy (AST) on the incidence or clinical outcomes of bladder cancer. Methods: We systematically searched the PubMed and Embase databases from inception to June 20, 2021 to identify all observational studies examining the incidence or clinical outcomes of bladder cancer in patients who received AST. AST is defined as the use of 5-alpha reductase inhibitors (5-ARIs) or androgen deprivation therapy (ADT). Results: A total of 18 observational studies were included. Our results showed that AST was not significantly associated with a reduced risk of BCa incidence (OR: 0.92, 95% CI: 0.68–1.24) compared with the lack of AST. The subgroup analysis revealed that finasteride use was significantly associated with a reduction in the risk of BCa incidence (OR: 0.75, 95% CI: 0.64–0.88). Recurrence-free survival (RFS) was improved among AST users compared with nonusers (HR: 0.68, 95% CI: 0.48–0.95), while no significant difference between AST users versus nonusers was identified for cancer-specific survival (CSS), overall survival (OS) or progression-free survival (PFS). Conclusion: Current evidence indicates that therapy with finasteride may represent a potential strategy aimed at reducing BCa incidence. Moreover, AST has a beneficial effect on the recurrence of bladder cancer. Further well-designed randomized trials or cohort studies with better characterized study populations are needed to validate our preliminary findings.